Student Engagement in Online Learning Among Undergraduate Nursing Students - Firman Sugiharto; Ryan Hara Permana; Yanti Hermayanti (Jurnal Keperawatan Komprehensif (Comprehensive Nursing Journal), 2023)
Aims: Student engagement (SE) is a significant factor for success in online learning. The low of SE will impact students' academic achievement. Purpose: This study aimed to describe SE in online learning at the Faculty of Nursing, Universitas Padjadjaran.  Methods: This study was quantitative descriptive research. The population was undergraduate nursing students (N=862). The sample criteria were that respondents were active students of the Faculty of Nursing, Universitas Padjadjaran for the 2020/2021 period from the Jatinangor and Pangandaran campuses. The sampling technique was total sampling with a response rate of 64,3% (n=554). Data were collected using the Online Community and Student Engagement Scale. Data were analyzed using descriptive statistics and presented in frequency distribution tables.  Results: The results showed that more than half of students (52.7%) had a low category of SE, and nearly half (47.3%) have shown a high category of SE in online learning. Students had low levels of Community Building with the Instructor, Community Building with Classmates, and Engagement with Learning (57.4%; 58.3%; and 51.8%, respectively). The SE level that the respondent currently has has the potential to be increased along with the ongoing process during the lecture period. Conclusion: More than half of students had a low category of SE in online learning this could have a negative impact on student achievement and educational completion rates. Therefore, intense interactions through discussions between students and lecturers, constructive feedback, and motivational support are highly recommended to be provided by the faculty and peers for improving the SE.